Techniques of Quality Management in Teams: Brainstorming - Stepanić, Josip (Array, 2014)
Brainstorming technique is described, various contexts of its application are presented, and its prerequisites are evaluated. Brainstorming is both a quality management technique and skill, and also a complex phenomenon that entails thorough understanding of social, cognitive, economic, pragmatic, cultural, communicational and other factors that influence its course. In the paper this phenomenon is analysed in the broader framework of dialogue, as a widely known and used, as well as a gravely criticised and much disputed method of breaking hierarchical pattern relationships and reaching creative solutions by walking along the thin line of ‘co-opetition’ where cooperation and competition merge and are combined in a higher synthesis. In the article brainstorming is analysed primarily for researchers and modellers of brainstorming as group work phenomenon.